Austria : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper focuses on the medium-term budgetary framework (MTBF) for Austria. Austria is part of a trend among many countries to consider some form of MTBF. This paper describes the proposed framework in Austria and assesses it in light of the experience of other countries. The general conclusion is that the track records are mixed, but that, on balance, the experiences with MTBFs have been favorable. The paper also examines the long-term fiscal challenges arising from demographic change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet